Capital punishment - Berlatsky, Noah Detroit, Mich., [c.2010] c.2010.; Greenhaven Press; Bible Society of South Africa; Berlatsky, Noah Detroit, MI, [c.2010] c.2010.; Greenhaven Press; Bible Society of South Africa (Detroit: Greenhaven Press, 2010)
A collection of essays dealing with capital punishment in the world.
Includes bibliographical references and index.
Adult
Keywords: Berlatsky, Noah Detroit, MI, [c.2010] -- c.2010.; Greenhaven Press; Imagined South Africa; Kabbala; Agriculture -- Environmental aspects -- United States; South Africa; Aufsatzsammlung